(untitled) (Bulletin KNOB, 2013)
The ‘Zaanse Schans’ (Zaandam Sconce) is a ‘reservation’ of transferred monuments and windmills from the Zaan region, which lies just north of Amsterdam. A comparison with open-air museums, however, doesn’t stand up. The site is freely admissible and there are residential areas. The article at hand explores the founding and realisation of the Zaanse Schans. What was unique for the Netherlands was that fifty years ago, moving these monuments was seen as the only option to preserve them. At the time, the typical wooden structures of the Zaan region were rapidly being displaced by industry. In response to the demolition several civil initiatives devoted themselves to preserving the regional architecture. The actual initiative to create the Zaanse Schans started during the Second World War when volunteers began to document old buildings and the first buildings to be demolished were put in storage. The municipality of Zaandam made a location available at the western side of the Kalverpolder, where a village on the banks of the Zaan River could be built from scratch. The idea was to realise an authentic ensemble. In the eyes of the pioneers ‘authenticity’ was considered A) a consistent urban development design on an appropriate location in the landscape (credible structure), B) a complete transfer and exact reconstruction of monuments (faithful in form), and C) having people live in the transferred houses (continuity of function). From the opening in 1965, the Zaanse Schans attracted many visitors, but not much thought had been given to what the experience offered to tourists might be exactly and what sort of facilities were required. Chaos ensued and visitors left in disappointment. A visit by a local councillor to Colonial Williamsburg (USA) became a turning point: the Zaanse Schans would henceforth focus on tourism. New facilities were built in such a way that they more or less fitted within the historical narrative. Since the mid-1970s, the Zaanse Schans has remained essentially unchanged. The municipality guarded and managed the protected village view, but the development of the site as a tourist attraction was left to entrepreneurs and they created the ‘brand’ Zaanse Schans according to their own views. For instance, they created free museums about wooden shoes and cheese that were mainly aimed at selling merchandise. As the commercial exploitation was completely separate from the management of the monuments and the site, the budget was never balanced and the municipality always had to make up the deficit. Now that subsidies are dwindling, the Zaanse Schans is compelled to expand its operation, with the goal of strengthening tourism and persuade visitors to stay longer. The ambition still is, as it was fifty years ago, to create the idea of a village ‘as it could have been in 1850’. The additions are built in the traditional local style of wood construction: new buildings based on regional typologies, materials, colours and details. A problem with this is that each party involved has its own ideas about what the Zaanse Schans essentially is. In the absence of a central controlling agency the quality of the site as a museum (authenticity and integrity of materials) is suffering. The idea from the founding years to make it a normal residential area has led to fragmented ownership and clashing interests, among other things. Unfortunately, it has now become almost impossible to preserve, let alone further develop the site’s exceptional value.